THE STATE, PROBLEMS AND PROMISING AREAS OF SCIENTIFIC RESEARCH IN VOLLEYBALL - Abatova Gulzar Nurlanovna (PEDAGOGS, 2024)
Abstract: Volleyball in modern sports firmly occupies a leading position in popularity and entertainment. The mass distribution of volleyball is facilitated by television, the Internet and other sources of information. The increased level of technical equipment of sports competitions affects the quality of the game itself.